Noncontact laser ultrasonic inspection of Ceramic Matrix Composites (CMCs). (June 2017) - Quintero, R.; Simonetti, F.; Howard, P.; Friedl, J.; Sellinger, A.
Abstract: Ceramic matrix composites (CMCs) are poised to revolutionize jet engine technology by enabling operation temperatures well beyond those possible with current superalloys, while reducing active cooling requirements and engine weight. Manufacturing of parts formed by silicon-carbide (SiC) fibers in a SiC matrix is now well advanced, with the first non-structural static components entering service in 2017 with the CFM Leap ® engine that uses SiC/SiC turbine shrouds. In order to expand the scope of application of CMCs to rotating parts, such as turbine blades, much work is being conducted to understand and characterize the modes of failure of these materials at temperatures beyond ∼ 1100 ° C . In this context, the ability of nondestructively monitoring the formation and progression of damage in CMCs specimens during high-temperature mechanical testing is critical. However, the elevated temperature precludes the possibility of using sensors placed in direct contact with the specimen and therefore severely restricts the range of available NDE techniques. This paper provides the first experimental assessment of the feasibility of noncontact laser ultrasonic inspection of SiC/SiC flat coupons. An Nd: Yag laser is used to excite ultrasonic waves on one side of the specimen while a Michelson interferometer detects the signals emerging on the other side at the epicenter position. The lasers are mounted on synchronized linear stages to form C-scans as in conventional immersion ultrasonics while ablation damage to the surface of the specimen is prevented by operating the lasers at low power density. Despite the complex microstructure of the SiC/SiC material it is found that the measured waveforms are remarkably similar to those observed when conducting the same tests in aluminum specimens. Moreover, it is shown that it is possible to image interlaminar defects caused by impacts, and monitor crack opening under tensile load. Finally, very good signal stability is observed when temperature is increased from 25 to 1250 °C which confirms the feasibility of laser monitoring at high temperature and is consistent with the good thermal stability of ceramic materials.